Artificial Intelligence for Inclusive Language Education: Bridging English and Indonesian Language Pedagogy in Higher Education - Deny Gunawan Susandi; Mohamad Irvan Septiar Musti; Murtini Murtini; Erma Damayanti; Nur Adi Setyo (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Inclusive education within the framework of Education for All requires pedagogical innovation that responds to diverse learner needs, including linguistic diversity, socio-economic disparities, varied proficiency levels, and digital access differences. In multilingual higher education contexts, English and Indonesian language programs face challenges in designing equitable and adaptive instruction. This qualitative interpretive study investigates how Artificial Intelligence (AI) can bridge English and Indonesian language pedagogy to support inclusive practices in university classrooms. Data were generated through semi-structured interviews, focus group discussions, and document analysis involving lecturers from both departments, and analyzed using reflexive thematic analysis. Findings indicate that AI is perceived as a pedagogical augmentation tool that can scaffold academic literacy, support differentiated instruction, and expand multilingual participation when aligned with inclusive design principles. However, participants also raised concerns regarding digital divides, algorithmic bias, and ethical governance. The study proposes an equity-driven conceptual framework positioning human-AI collaboration as a mediational strategy for inclusive language education in higher education.